On the soliton solutions to the Nizhnik-Novikov-Veselov and the Drinfel'd-Sokolov systems - Cattani, Carlo; Sulaiman, Tukur Abdulkadir; Baskonus, Haci Mehmet; Bulut, Hasan (Springer, 2018)
This study investigates the Nizhnik-Novikov-Veselov and the Drinfel'd-Sokolov systems by using the extended sinh-Gordon equation expansion method. The Nizhnik-Novikov-Veselov system is an isotropic Lax extension of the one-dimensional Kortewegde Vries equation and the Drinfel'd-Sokolov system is a nonlinear model that possesses some special forms of Lax pairs. Topological kink-type, topological, non-topological, compound topological-non-topological bell-type and singular soliton solutions are successfully constructed. Under the choice of suitable values of parameters, the 2D, 3D and contour graphs to some of the obtained solutions are plotted.
Keywords: The extended ShGEEM; The NNV and the DS systems; Soliton solutions